EMERGENCY NEUROMUSCULAR ADMISSIONS ARE AVOIDABLE: A REGIONAL AUDIT OF UNPLANNED HOSPITAL ADMISSIONS OF NEUROMUSCULAR PATIENTS 2009–2011: FINAL RESULTS AND RECOMMENDATIONS. Issue 11 (9th October 2013) - Jaffer, Fatima; Reilly, Mary M; Quinlivan, Ros; Muntoni, Francesco; Turner, Christopher; Parton, Matthew; Lunn, Michael; Hilton–Jones, David; Korkodilos, Marilena; Hanna, Michael G
Abstract : Introduction: Neuromuscular diseases (NMD) require long–term multi–disciplinary care. In 2010–11 there were 5.3 million emergency admissions of which 213, 000 related to neurological disorders. 13% of these (∼28, 000) were secondary to NMD. With each admission costing ∼£3000 per day, it is estimated that this leads to costs of £81 m nationally (£28 m in four specialised commissioning groups [SCG]: London, East of England, South–East Coast and South–Central). Fundamentally, avoidable admissions have an adverse effect on quality of life. Studies have shown that strengthening links between specialist and primary care, integration of health and psychosocial care and hospital at home interventions are associated with lower emergency admission rates. The aims were to: 1. Determine the proportion of avoidable emergency admissions directly attributable to NMD 2. Determine what proportion of patients are known to specialist neuromuscular services and compare characteristics of such admissions against centres without a specialist service 3. Identify reasons for emergency admissions and preventable measures. Methodology: A retrospective case note audit was conducted across 12 trusts in four SCG regions. Emergency admissions in patients with NMD were identified by SCG IT teams using secondary user services data and ICD–10 codes for neuromuscular and metabolic disorders between January 2009 and June 2011. In the absence of national clinical standards of care for NMD, consensus criteria to identify avoidable admissions were developed by an expert panel (Table 1). Data analysis was undertaken independently by London SCG. Results: There were 576 unplanned admissions for 395 patients. Of 395 patients, 65% had a pre–existing NMD and 25% of these were known to specialist NMD services. Of 576 separate admissions, 65% were at hospitals with a specialist service and 74% of these admissions were in patients with a pre–existing NMD. Overall, 37.5% of unplanned admissions were avoidable and 5% potentially avoidable. Further analysis showed that of the admissions directly attributable to NMD, 63% were avoidable and 5.7% potentially avoidable. There was no difference in preventability of admissions between hospitals with and without specialist NMD services (p=0.79). The main measures that may have prevented an avoidable admission were: On–going disease monitoring, access to specialist services (nurse specialist, therapists, equipment and cardiorespiratory care), and implementation of an emergency plan. 20% of patients known to NMD services had a documented emergency plan. 58% of inpatients were reviewed by a neurologist. Conclusions: Over one–third of emergency admissions were avoidable, majority occurring in patients with pre–existing NMDs. Only a quarter of neuromuscular patients are known to a specialist and 20% have an emergency plan in place. Key recommendations were developed for the national working specification after consultation with the All Party Parliamentary Group for Muscular Dystrophy to reduce fragmentation of care. These are: 1. Monitoring of patients and access to neuromuscular services between appointments 2. Specialist NMD centres to lead coordination of care across sub–specialties 3. Strengthen links with social services and local hospitals to enable advice 4. All patients with a known NMD should have a documented referral to the neurology team during admission and an emergency plan on discharge.